Patterns of Sexually Transmitted Co-infections and Associated Factors Among Men Who Have Sex With Men: A Cross-Sectional Study in Shenyang, China - Ye, Ze-Hao; Chen, Shuo; Liu, Fan; Cui, Si-Tong; Liu, Zhao-Zhen; Jiang, Yong-Jun; Hu, Qing-Hai (Frontiers in Public Health, 2022)
Background: Men who have sex with men (MSM) are disproportionately affected by sexually transmitted infections (STIs). We sought to describe patterns of sexually transmitted co-infections and explore factors associated with increased acquisition of STIs among MSM. Methods: We enrolled MSM in Shenyang, China, between July and December 2020 to test for five STIs, including human papillomavirus (HPV), herpes simplex virus 2 (HSV-2), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Treponema pallidum (TP). Data regarding demographic and behavioral characteristics of participants were collected through a self-administered digital questionnaire. We adopted the ordinal logistic regression model to identify factors associated with acquiring more STIs. Results: Overall, 177 participants with completed test results for all five STIs were analyzed. These participants had a median age of 29.0 (interquartile range: 23.0−38.0) years. The prevalence of STI co-infections was 33.3% (59/177; 95% confidence interval [CI], 26.8–40.6%), among which HPV/HSV-2 (34.9%) and HPV/HSV-2/TP (31.3%) co-infection were the predominant type among participants with dual and multiple infections, respectively. Participants who were aged ≥50 years (adjusted odds ratio [aOR], 4.20; 95% CI, 1.49–11.88; P = 0.007), had a history of STIs (aOR, 3.25; 95% CI, 1.60–6.61; P = 0.001) and unprotected anal intercourse (aOR, 1.95; 95% CI, 1.04–3.66; P = 0.037) were positively associated with acquiring more STIs. Conclusions: MSM suffer a substantial burden of sexually transmitted co-infections. An optimized multi-STI integration strategy targeting prevention, surveillance, screening, and treatment is warranted to reduce the prevalence of sexually transmitted co-infections, especially in older MSM.